Situational Analysis - Kevin D. Hoover (Duke University, Center for the History of Political Economy (CHOPE), 2016)
Situational analysis (also known as situational logic) was popularized by Karl Popper as an appropriate method for the interpretation of history and as a basis for a scientific social science. It seeks an objective posit ive explanation of behavior through imputing a dominant goal or motive to individuals and then identifying the action that would be objectively appropriate to the situation as the action actually taken. Popper regarded situational analysis as a generalization to all of social science of the prototypical reasoning of economics. Applied to history, situational analysis is largely an interpretive strategy used to understand individual behavior. In social sciences, however, it is applied many to types of beh avior or to group behavior (e.g., to markets) as is used to generate testable hypothesis. Popper's account of situational analysis and some criticisms that have been levied against it are reviewed. The charge that situational analysis contradicts Popper's view that falsification is the hallmark of sciences is examined and rejected: situational analysis is precisely how Popper believes social sciences are able to generate falsifiable, and, therefore, scientific hypotheses. Still, situational analysis is in tension with another of Popper's central ideas: situational analysis as a method for generating testable conjectures amounts to a logic of scientific discovery, something that Popper argued elsewhere was not possible.
Keywords: B40; B41; D01; A12; 330; Situational analysis; situational logic; Karl Popper; falsification; context of discovery; context of justification